An Introduction to Mining Tourism Route in Yazd Province - Neda Torabi Farsani; Seyed Reza Bahadori; Seyed Abolghasem Mirzaei (Geoconservation Research, 2020)
Nowadays, mining tourism is known as a strategy for local development and an alternative economy in remote areas. Yazd province is Iran's mineral hub and has a high potential for promoting mining tourism. However, this form of tourism in the province has not been considered as it should. This paper emphasizes on recognizing the mining tourism routes in Yazd province. Field trip and observation method were used in this research, and the results identified four routes (Taft-Mehriz route; west of Meybod city; the route from Yazd to Tabas and The distance between Bafgh and Bahabad) for promoting mining tourism in the province.